2014
DOI: 10.1103/physrevlett.112.014101
|View full text |Cite
|
Sign up to set email alerts
|

Phase Synchronization of Two Anharmonic Nanomechanical Oscillators

Abstract: We investigate the synchronization of oscillators based on anharmonic nanoelectromechanical resonators. Our experimental implementation allows unprecedented observation and control of parameters governing the dynamics of synchronization. We find close quantitative agreement between experimental data and theory describing reactively coupled Duffing resonators with fully saturated feedback gain. In the synchronized state we demonstrate a significant reduction in the phase noise of the oscillators, which is key f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
178
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(180 citation statements)
references
References 39 publications
1
178
0
1
Order By: Relevance
“…Optomechanical systems [17] appear to offer a particularly promising approach. Recent experiments have reported classical synchronization of nanomechanical oscillators [18,19], the quantum many-body dynamics of an array of identical optomechanical cells has been predicted to show synchronized behavior [9], and quantitative measures for quantum synchronization based on the Heisenberg uncertainty principle have been applied to two and many coupled optomechanical cells [10].…”
mentioning
confidence: 99%
“…Optomechanical systems [17] appear to offer a particularly promising approach. Recent experiments have reported classical synchronization of nanomechanical oscillators [18,19], the quantum many-body dynamics of an array of identical optomechanical cells has been predicted to show synchronized behavior [9], and quantitative measures for quantum synchronization based on the Heisenberg uncertainty principle have been applied to two and many coupled optomechanical cells [10].…”
mentioning
confidence: 99%
“…Several experimental works have shown that synchronization can be observed in the laboratory within Josepshon junction arrays [40], nanomechanical systems [17], or optomechanical systems [41]. All of these systems share one prominent property: They behave quantum mechanically at sufficiently low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is not doubt about the fundamental importance of studying quantum fluctuations within the emergence of synchronized states [9][10][11][12][13][14][15][16]. Moreover, the Kuramoto model has been implemented on circuits and microand nanomechanical structures [17,18], systems that have already met the quantum domain [19,20]. At the quantum level, synchronization, understood as the emergence of a coherent behavior from an incoherent situation in the absence of external fields, is reminiscent of phenomena such as Bose-Einstein condensation and has been observed in interacting condensates of quasiparticles [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, their strong nonlinearity, tunability, and convenient time scales make detailed experimental studies of synchronization possible, including the observation of features such as phase slipping, phase locking, phase inertia, and phase oscillation. 4,[7][8][9][10] Compared to top-down fabricated NEMS devices, graphene nanomechanical systems offer enhanced nonlinear response due to their extreme aspect ratio. This enables new experimental studies of parametric synchronization and phaseoscillation dynamics, which are the topics of this letter.…”
mentioning
confidence: 99%
“…[3][4][5][6] To study these phenomena experimentally, NanoElectroMechanical Systems (NEMS) have been proposed as representative model systems. Indeed, their strong nonlinearity, tunability, and convenient time scales make detailed experimental studies of synchronization possible, including the observation of features such as phase slipping, phase locking, phase inertia, and phase oscillation.…”
mentioning
confidence: 99%